Ecotourism in Nicaragua - Fransson, Therese (2007)
Between the years of 1990 and 2000, the number of tourists increased with more than hundred percent globally, and more than three hundred percent in Nicaragua. Further, this industry contributes to eleven percent of the gross domestic product of the world and is, from an economic point of view, regarded as one of the biggest industries worldwide. However, tourism often conveys negative secondary effects on the local environment and contributes to unfair use of local cultures for commercial purposes.